Respuesta :

Answer:

46

Step-by-step explanation:

First you need to solve.. So put 3x - 10 and 2x + 1 together as one equation.

It should look like this:

3x - 10 = 2x + 1

Now you just need to solve it.

1) First you add 10 on both sides.

3x - 10 = 2x + 1

   + 10 =    + 10

------------------------

     3x = 2x + 11

2) Then you subtract 2x on both sides.

     3x = 2x + 11

   - 2x =- 2x + 11

-------------------------

      x = 11

3) Now you plug in 11 for x.

3x - 10 = 2x + 1

Like this:

3(11) - 10 = 2(11) + 1

33 - 10 = 22 + 1

23 =23

So C to E and E to A = 23

To get from C to A just add 23 + 23 which is 46. And that is ur answer.

Answer:

it is 46

Step-by-step explanation:

First you need to solve.. So put 3x - 10 and 2x + 1 together as one equation.

It should look like this:

3x - 10 = 2x + 1

Now you just need to solve it.

1) First you add 10 on both sides.

3x - 10 = 2x + 1

  + 10 =    + 10

------------------------

    3x = 2x + 11

2) Then you subtract 2x on both sides.

    3x = 2x + 11

  - 2x =- 2x + 11

-------------------------

     x = 11

3) Now you plug in 11 for x.

3x - 10 = 2x + 1

Like this:

3(11) - 10 = 2(11) + 1

33 - 10 = 22 + 1

23 =23

So C to E and E to A = 23

To get from C to A just add 23 + 23 which is 46. And that is ur answer.

you can slove this in this way if want more explansion ask me